PENGARUH STRATEGI PEMASARAN BERBASIS SYARIAH TERHADAP KEPUTUSAN MEMBELI PRODUK HNI-HPAI PADA MASYARAKAT URBAN DAN RURAL DI PROVINSI JAMBI - Mawar Indah (Lembaga Pengembangan Kinerja Dosen, 2023)
Factors that can foster buying decisions are related to emotions, someone feels happy and satisfied in buying goods or services, then it will strengthen buying interest. Through this research, it is expected to find out the to reveal the influence of sharia-based marketing strategies on the decision to buy HNI-HPAI products in Urban and Rural communities in Jambi Province The type of research in this thesis is field research, using quantitative research methods. The object of research used in this research is Urban and Rural communities in Jambi Province From the results of the research conducted, it is shown that: there is an influence of marketing strategy and buying decisions on the decision to buy HNI-HPAI products in Urban and Rural communities in Jambi province because the marketing strategy calculation (X) t value is greater than t table, namely ( 4,094 > 2,159) and a significance value of 0.000 < 0.05 then Ho is rejected and Ha is accepted besides that because the products offered are HNI-HPAI products in accordance with consumer desires, all product choices are kaffah (according to religious norms), product quality is able to compete with product quality other.